2020
DOI: 10.1097/mpg.0000000000002833
|View full text |Cite
|
Sign up to set email alerts
|

Vedolizumab Trough Levels in Children With Anti‐Tumor Necrosis Factor Refractory Inflammatory Bowel Disease

Abstract: Objectives: Inflammatory bowel disease (IBD) can be successfully treated with vedolizumab. Studies in adult IBD patients have shown that differences in response to vedolizumab may be related to variability in vedolizumab trough levels, but in children with pediatric-onset IBD data regarding vedolizumab trough levels are not available. Thus far, the role of trough levels in pediatriconset IBD treatment remains unclear. We aimed to investigate predictors of vedolizumab trough levels in pediatric-onset IBD patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 32 publications
4
15
1
Order By: Relevance
“…As noted, vedolizumab PK analysis in children has been limited to sparse clinical trial data sets or data from small cohorts. These studies found elevated inflammatory markers (including CRP and FCP) and longer intervals between infusions were associated with lower cTrough 11 . Of note, CD patients had lower cTrough levels at week 2 (infusion‐2) and week 6 (infusion‐3) than UC/IBD‐U patients 11 which was also seen in this current cohort study at infusion‐4.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…As noted, vedolizumab PK analysis in children has been limited to sparse clinical trial data sets or data from small cohorts. These studies found elevated inflammatory markers (including CRP and FCP) and longer intervals between infusions were associated with lower cTrough 11 . Of note, CD patients had lower cTrough levels at week 2 (infusion‐2) and week 6 (infusion‐3) than UC/IBD‐U patients 11 which was also seen in this current cohort study at infusion‐4.…”
Section: Discussionsupporting
confidence: 77%
“…These studies found elevated inflammatory markers (including CRP and FCP) and longer intervals between infusions were associated with lower cTrough 11 . Of note, CD patients had lower cTrough levels at week 2 (infusion‐2) and week 6 (infusion‐3) than UC/IBD‐U patients 11 which was also seen in this current cohort study at infusion‐4. In Phase II paediatric clinical trial, UC clinical responders had higher week 14 cTroughs than non‐responders while no difference in cTrough was noted in the CD patients when stratified by the outcome 12 …”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…However, according to data from a TDM study in adult IBD, VDZ trough levels of >30 μg/mL at week 2, >24 μg/mL at week 6, and >14 μg/mL during maintenance therapy have been proposed for achieving clinical remission [ 19 ]. In another study in pediatric-onset IBD patients treated with VDZ, the mean VDZ trough level was 29.9 μg/mL at week 6 and 11.5 μg/mL during maintenance therapy [ 20 ]. In this case report, VDZ trough levels were lower than the proposed threshold targets; however, the patient responded well.…”
Section: Discussionmentioning
confidence: 99%
“…A recent Dutch study highlighted the exposure–efficacy relationship of VDZ in a pediatric IBD population which had failed anti-TNF. The authors concluded that a lower TL of VDZ in Crohn's disease patients vs. UC/IBD-U was due to the transmural nature of the disease and may benefit from proactive TDM and subsequent higher dosing ( 45 ).…”
Section: Methodsmentioning
confidence: 99%